2016
DOI: 10.1152/ajprenal.00406.2015
|View full text |Cite
|
Sign up to set email alerts
|

Sulfate and thiosulfate inhibit oxalate transport via a dPrestin (Slc26a6)-dependent mechanism in an insect model of calcium oxalate nephrolithiasis

Abstract: Nephrolithiasis is one of the most common urinary tract disorders, with the majority of kidney stones composed of calcium oxalate (CaOx). Given its prevalence (US occurrence 10%), it is still poorly understood, lacking progress in identifying new therapies because of its complex etiology. Drosophila melanogaster (fruitfly) is a recently developed model of CaOx nephrolithiasis. Effects of sulfate and thiosulfate on crystal formation were investigated using the Drosophila model, as well as electrophysiological e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Indeed, the Drosophila homolog of SLC26A6 (encoding dPrestin) seems to have conserved chloride and oxalate exchange function and has been used very recently to explore therapeutic inhibitors of calcium oxalate crystallization. 84 Such basic biologic research may have important future translational effects in human stone disease.…”
Section: Progress In Animal Models Of Nephrolithiasismentioning
confidence: 99%
“…Indeed, the Drosophila homolog of SLC26A6 (encoding dPrestin) seems to have conserved chloride and oxalate exchange function and has been used very recently to explore therapeutic inhibitors of calcium oxalate crystallization. 84 Such basic biologic research may have important future translational effects in human stone disease.…”
Section: Progress In Animal Models Of Nephrolithiasismentioning
confidence: 99%
“…Mutations of Slc26a6 have been identified from patients with nephrolithiasis. It also has been shown that RNAi knockdown of dPrestin specifically in principal cells, the Drosophila homolog of Slc26a6, led to decreased calcium oxalate stone formation in Malpighian tubules (Landry et al, 2016). These results strongly suggest that fruit fly could be an ideal genetic kidney stone disease model to screen novel genes involved in the pathogenesis of nephrolithiasis and validate the function of candidate genes identified from patients with nephrolithiasis in vivo (Hirata et al, 2012a).…”
Section: Introductionmentioning
confidence: 83%
“…One of the limited treatments available for humans is consumption of citrate, as metal citrate salts tend to be highly soluble. Administration of citrate (Chen et al 2011;Ho et al 2013), thiosulfate, or sulfate (Landry et al 2016) in Drosophila similarly reduces stone burden and extends lifespan.…”
Section: Modeling Disease Processesmentioning
confidence: 98%